Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite

Synthesis and biological evaluation of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives via click chemistry approach - Kategaonkar, Amol H.; Shinde, Pravin V.; Kategaonkar, Atul H.; Pasale, Sharad K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (European Journal of Medicinal Chemistry, 2010)
Synthesis of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives (4a-h) using 1,3-dipolar cycloaddition (click chemistry) reaction of 3-(azidomethyl)-2-chloro-quinoline derivatives (3a-h) with phenyl acetylene in the presence of Cu(I) catalyst has been achieved in very high yield. These molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 2; 2-Chloro3-formyl quinoline; 3-Triazole; Antibacterial; antifungal; Click chemistry